Functional Recovery after Revision Anterior Cruciate Ligament Reconstruction with a Second Autograft: A Matched Cohort Analysis in Adolescent Patients (197). Issue 10 (31st October 2021) - Wilson, Benjamin; Heyworth, Benton; Coene, Ryan; Sugimoto, Dai; Micheli, Lyle; Kocher, Mininder; Christino, Melissa
Objectives: Young patients are the highest risk demographic for ACL graft failure and revision surgery. Previous studies have shown higher rates of graft failure with the use of allograft tissue for ACL reconstruction (ACLR) in both primary and revision surgeries. However, questions remain regarding the functional consequence of harvesting a second autograft from the ipsilateral knee for revision ACLR. The purpose of this study was to evaluate 6-month functional testing in patients who underwent revision ACLR with use of a second autograft from the ispilateral knee, when compared to matched cohorts of primary ACLR patients. Methods: A retrospective review of prospectively collected data from patients aged 19 or younger who underwent revision ACLR with a second autograft of an opposite muscle group (either revision patellar tendon (BTB) following primary hamstring (HS) or revision HS following primary BTB) at the study institution was performed. Exclusion criteria were patients who underwent iliotibial band autograft ACLR, those with two autografts from synergistic muscle groups, grafts from the contralateral knee, debilitating injury or surgery to the contralateral lower extremity, and multi-ligamentous knee injury. All subjects underwent functional return to sports (RTS) testing 5-8 months after revision surgery, which included anthropometric measures, isometric strength, Y-Balance, and functional hop testing. Side-to-side deficits were then compared using standard limb symmetry index (LSI) metrics, after matching a cohort of primary ACLR patients based on age, sex, and body mass index (BMI). Multivariate analysis of variance (MANOVA) was used to compare RTS metrics, and if significance was detected, pairwise comparison was performed by Bonferroni post-hoc correction. Statistical significance of p<0.05 was applied. Results: The cohort of 37 revision ACLR patients were compared to cohorts of 62 primary HS and 47 BTB ACLR patients, respectively (Table 1). The revision cohort showed comparable knee extension strength deficits to the BTB cohort (-9.45±12.09% vs -8.81±13.83%, p=0.999), which were significantly greater than that of the HS cohort (-9.45±12.09% vs -0.99±12.00%, p<0.05). Greater knee flexion strength deficits were seen in the HS cohort than the revision cohort (-38.90±16.21% vs -28.13±23.22%, p=0.009), whose deficits were, in kind, significantly greater than that of the BTB cohort (-28.13±23.22% vs -1.17±12.41%, p=0.001). The HS cohort also showed greater triple hop deficit (-21.08±25.99%) than the other two cohorts (-21.08±25.99% vs -10.75±12.85 vs -6.84±23.81, p=0.024), which were not significantly different from each other. Conclusions: After revision ACLR with a second autograft from the opposing muscle group of the ipsilateral knee, adolescents show similar knee extension strength deficits compared to primary ACLR patients with BTB grafts, but improved knee flexion strength deficits compared to primary ACLR patients with HS grafts.